Effect of Adding Biomin as a Natural Growth Promoter on Productive Performance, Some Haematological and Immunological Traits of Broiler Chicks - EL-Kaiaty , A.M.; Mohamed, F.R.; Abdel-Kareem, A.A.A.; Eita, E.M. Abou; Eshra, A.A.M. (International Journal of Poultry Science, 2015)
The objective of the present study was to investigate the effect of adding Biomin as a natural growth promoter in drinking water on the productive performance, some hematological and immunological parameters in broiler chicks. A total of 180 unsexed, one day old, broiler chicks (Hubbard) were weighed, wing banded and randomly classified to three equal groups. All chicks in the 1st group were watered fresh tap water during the experiment, while those in the 2nd and 3rd groups were orally received fresh tap water including 20 and 30 mg Biomin/chick during the first three days of age. All chicks were fed on commercial basal diets ad libitum and daily exposed to 24 lighting hours allover experimental period. All birds were reared on a partitioned deep litter floor. The obtained results could be concluded as follow: The oral administration of Biomin to broiler chicks increased (p<0.05) body weight and body weight gain from 2 to 6 weeks of age in the treated groups than those of the control. The treated broilers chicks with Biomin at 20 and 30 mg/chick consumed less feed intake and had better feed conversion ratio all over experimental period than those of the control. Hemoglobin, hematocrit (%), globulin, total lipids, glucose and ALT for chicks orally received biomin at 20 and 30 mg/bird insignificantly affected as compared to control. Total cholesterol level in the treated group decreased significantly (p<0.05) at 2 and 4 weeks of age as compared with those of control. Creatinine and AST levels for treated chicks were significantly affected by the Biomin administration at 4 and 6 weeks of age. Humoral immune response for treated chicks against sheep red blood cell (SRBC, s) insignificantly increased as compared with control chicks. Similarly, the immune response (Antibody titer) for Newcastle disease (ND) was insignificantly affected with Biomin treatment.